Porous carbon architectures with different dimensionalities for lithium metal storage. Issue 1 (31st December 2022) - Qutaish, Hamzeh; Han, Sang A; Rehman, Yaser; Konstantinov, Konstantin; Park, Min-Sik; Ho Kim, Jung
ABSTRACT: Lithium metal batteries have recently gained tremendous attention owing to their high energy capacity compared to other rechargeable batteries. Nevertheless, lithium (Li) dendritic growth causes low Coulombic efficiency, thermal runaway, and safety issues, all of which hinder the practical application of Li metal as an anodic material. In this review, the failure mechanisms of Li metal anode are described according to its infinite volume changes, unstable solid electrolyte interphase, and Li dendritic growth. The fundamental models that describe the Li deposition and dendritic growth, such as the thermodynamic, electrodeposition kinetics, and internal stress models are summarized. From these considerations, porous carbon-based frameworks have emerged as a promising strategy to resolve these issues. Thus, the main principles of utilizing these materials as a Li metal host are discussed. Finally, we also focus on the recent progress on utilizing one-, two-, and three-dimensional carbon-based frameworks and their composites to highlight the future outlook of these materials. Graphical abstract: uf0001